Police reform in Africa:theory, policy and practice in the making?' - Van Der Spuy, Elrena (2016)
The nature of police agencies on the payroll of the state in Africa remains illresearched and by implication ill-understood. An Africa-wide police studies is still to be developed, although recent contributions are beginning to set instructive examples to those eager to participate. In search of more details regarding police reform, how it is conceptualised on the one hand, and practised on the other, this paper engages with the substantive deliberations of five workshops on police reform which took place in a number of locations in Africa between June 2006 and May 2007. Each of the five workshops is subjected to interpretative reading and comparative analysis. The aim is to highlight the kinds of issues around which discussion on police in Africa have been taking place. Each of the deliberations yields some insight into the state of the public police in Africa; the policy frameworks in terms of which police reform is articulated; the perceived opportunities for reform; the strategies devised by social actors; and the range of obstacles which reform interventions confront. In the concluding section, the challenges confronting the development of an African police studies are very briefly considered